Quality Changes of Button Mushrooms (Agaricus bisporus) Under Different Storage Conditions - Fadhallah, Esa Ghanim; Herdiana, Novita; Susilawati, Susilawati; Zulferiyenni, Zulferiyenni (Journal of Tropical Agricultural Engineering and Biosystems - Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2023)
Button mushrooms (Agaricus bisporus) have become an attractive agricultural product due to their high nutritional value and use as food. However, since it has a low shelf life, further storage condition needs to be studied. This research investigated the quality changes of button mushrooms under different storage conditions. The mushrooms were stored both in cold and room temperature. The treatments used are different packaging materials such as Styrofoam, polyethylene, and edible coating, where the unpacked mushroom is used as control. Observed parameters are sensory, water content, and weight loss. Button mushrooms with edible coating at cold and room temperature storage were determined as the best treatment that resulted in the lowest decrease in weight loss and water content. Based on this study, the recommended storage condition for button mushrooms is using edible coating in cold temperatures.